Drought induced problems and responses of small towns and rural water entities in Colorado: the 1976-1978 drought - Howe, Charles W., author; Alexander, Paul K., author; Goldberg, Jo Anne, author; Sertner, Steven, author; Studer, Hans Peter, author; Colorado Water Resources Research Institute, Colorado State University, publisher (Colorado State University. Libraries, 1980)
The climatological and hydrologic conditions across the State of Colorado during the 1976-1978 drought showed great diversity, adjacent drainage basins often experiencing quite different conditions. This emphasizes the importance of providing climatological information and assistance programs that are tailored to local areas (e.g. the Water Districts in Colorado). Small towns experienced the intensifying of problems that, for the most part, had existed for a long time: lack of adequate raw water; poor system performance and high loss of produced water from lack of maintenance; inadequate financing and the use of water revenues for general purposes; and, at times, inadequate management. The latter is often caused by high turnover as personnel are attracted to the larger towns. Town responses included emergency repairs, drilling wells, buying additional water rights and renting water from farmers, restrictions on water use, installation of meters, and increasing water charges (both price and flat rates). The town experience indicated that many effective counter-drought actions depend upon local knowledge and initiative. State and federal programs cannot substitute for this, so these higher level programs must be designed to stimulate local initiative and not to be "a reward for 50 years of bad management." Rural water entities providing mostly irrigation water experienced problems stemming in part from over-irrigation in the early season, over-expansion of acreage relative to reliable water supply, and inflexible reservoir management. Cooperative sharing of water and water rentals among farmers frequently helped avoid the economic inefficiencies that would occur under strict application of priority rights. This emphasizes the importance of facilitating both the short and long-term transferability of water among uses. Major opportunities exist for conjunctive management of surface and tributary groundwaters. The State priority rights system currently prevents rational conjunctive management.
Submitted to Office of Water Research and Technology, U.S. Department of the Interior.
June 1980.
Keywords: Water-supply, Rural -- Colorado; Droughts -- Colorado